A metrópole e a prosa cinematográfica no modernismo estadunidense: uma abordagem de Manhattan Transfer de John Dos Passos - Soler, Aline Shaaban [UNESP] (2015)
This study aims to present an analysis of the modernist novel Manhattan Transfer (1925), by the writer John Dos Passos. After introducing the author, the first chapter investigates the relations between Manhattan and the main literary modernist characteristics, intending to understand the reason why the work of Dos Passos has been in a second plan by the critics. We endorse the hypothesis that it occurs because Manhattan doesn‟t exactly coincide with what has been considered the essence of the modernism, presenting characteristics that are close to the realism. The second chapter purposes a Manhattan‟s cinematographic approach precisely in the sense of grasping the relation between modernist and realist characteristics. In order to do it, we start with the structural analysis of Dos Passos‟s work made by Pouillon and Sartre; and with the Griffith‟s and Eisentein‟s concept of montage. After that, we perform an analysis according to these theoretical references. The third chapter, based on the ideas of the second, is about New York and its representation in the novel and presents an analysis of three of the most important characters. In the final consideration, it is argued the significance of the idea of simultaneity, obtained thanks to a cinematographic prose with the purpose of depicting the metropolis, and the need of a reflexive and critic view to understand the relations that are presented in Manhattan